IMPROVING STUDENTS' EFFORT CAPACITY THROUGH MOVEMENT GAMES IN PHYSICAL EDUCATION LESSON - Andreea - Gabriela Lazăr (Editura Univeristatii "Stefan cel Mare" din Suceava, 2020)
Maintaining effort capacity is one of the goals pursued in adult physical education. Sedentary people have difficulty in sustaining an effort that is considered to be withing the usual intensity. They should receive training exercise because they have lost the physical ability through a bad conduct of life. In this research we started from the hypothesis that the use in the physical education lesson of motion games, which involves sustained efforts, will lead to a much faster increase of the students' effort capacity. Dynamic games will determine the students to participate with greater interest and pleasure in lessons, and this will result in improved effort due to their active involvement. The goal was to highlight that motion games can also be used with success in the case of young people. The attractiveness and dynamism that characterizes the games determines the students to be more active and more involved in practicing physical exercise. The experiment was conducted on a group of 18 students from the second year of study at Faculty of Economic Sciences and Public Administration, at "Ştefan cel Mare" University of Suceava. The control group was formed from 18 students in the second year, the same specialization in another study group. The experiment was conducted over a period of 4 months.